Foliar application of magnesium and the use of plant growth-promoting rhizobacteria improve photosynthetic physiology and the yield components of soybean - de Souza Júnior, Nelson Câmara; Girardi, Vitória Almeida Moreira; Olivio, Maiara Luzia Grigoli; Mendes, Thalita Fischer Santini; Matos, Aline Marchetti Silva; Ribeiro, Naiane Antunes Alves; Silva, Bárbara Pereira Christofaro; Galindo, Fernando Shintate; de Camargos, Liliane Santos; Andreotti, Marcelo (Frontiers in Plant Science, 2026)
IntroductionThe study evaluated the effects of foliar magnesium (Mg) application and inoculation/co-inoculation with plant growth-promoting rhizobacteria (PGPRs) on soybean physiological metabolism and yield in a long-term no-tillage system under Brazilian Cerrado conditions. Despite the relevance of PGPRs for crop resilience, there remains a research gap regarding the use of Priestia megaterium and Bacillus subtilis as stimulators of plant physiological metabolism under field conditions, particularly their potential to mitigate adverse climate-related stresses. The novelty of this study lies in the unprecedented assessment of the interaction between foliar Mg application and the inoculation of these bacteria in soil under a long-term no-tillage system. We investigate how this combination can enhance the crop’s physiological metabolism, contributing to refined agricultural management techniques that are essential for addressing the challenges posed by climate change.MethodsThe field experiment was carried out in an Oxisol over two growing seasons, using a randomized complete block design in a factorial scheme (3 x 2), combining three inoculation treatments (Bradyrhizobium, Bacillus subtilis, and Priestia megaterium) with or without foliar Mg application at the V6 soybean growth stage.ResultsThe control treatment (Bradyrhizobium japonicum) showed higher ureide content (approximately 25% greater than the seed co-inoculation treatment) and greater plant height in both growing seasons. Principal Component Analysis (PCA) indicated that the control was more susceptible to heat stress, as evidenced by higher MDA and peroxide levels. Furrow co-inoculation exhibited intermediate performance, with greater sensitivity to high temperatures in the 2023/24 season and lower water-use efficiency in 2024/25. In contrast, seed co-inoculation increased the number of pods (40%) and grains per plant (45%), enhanced gross photosynthesis (40%), instantaneous water-use efficiency (25%), and internal carbon concentration (10%), compared with the control in both evaluated seasons.ConclusionThe combination of seed co-inoculation with foliar Mg application reduced hydrogen peroxide content, suggesting mitigation of reactive compounds and greater physiological stability. In summary, seed co-inoculation associated with foliar Mg application improved physiological attributes and yield components of soybean under field conditions in the Cerrado.